(untitled) (Conference on English Language Teaching, 2023)
The development of distance learning in Indonesia started during the Covid-19 era and continues to the post-pandemic era. Schools and Universities in Indonesia began to develop distance learning programs to cover the need for students to study from their region as an effect of distance learning in the pandemic era to the regular offline classes. Distance learning requires students and teachers to cope autonomously with all learning materials. The role of teachers in helping students deal with the lesson is crucial. Thus, this study explores how teachers’ experience applying the supportive instructional practice in distance learning supports learners’ autonomy in the EFL context. Two English lecturers who teach English in a distance learning program were selected to share their experiences through the narrative inquiry method. This study shares how lecturers use supportive instructional practice in distance learning activities to support and activate students’ autonomy. Besides, lecturers’ past, current, and future experience in teaching English is essential to activate learners’ autonomy with supportive instructional practice. Educational practitioners must be aware that learning materials in distance learning might differ from in-class materials.